Social Marketing Approach: A Strategy to Improve the Quality of Children's Health in Communities - Getar Hati (Asian Social Work Journal, 2019)
This article describes children health’s issue as primary need to achieve their basic rights. In general, children are vulnerable to get nutrition inadequacy because they tend to consume unhealthy foods. Healthy food is a basic right that must be fulfilled to support children’s growth and development. I examined two research areas identified that the problem of children in consuming unhealthy foods does not always related to the family poverty problem. This article also describes the conditions in the poor communities in North Jakarta and the intermediate community in Depok, use descriptive studies. The findings showed that children’s behavior in consuming unhealthy food was due to several factors, including lack of knowledge and skills of parents or caregivers and also negative support from the social environment around children. In addition, cultural change and dynamic information technology development has greatly affected the children consumption habit. This article discusses the process description in implementing communication strategies applied for those two research areas which have different characteristics through the social marketing approach. This approach emphasizes the development of the role of all elements in the community and the intervention strategies applied in each area of the study.